Stand‐Alone Intrinsically Stretchable Electronic Device Platform Powered by Stretchable Rechargeable Battery. (13th September 2020) - Song, Woo‐Jin; Kong, Minsik; Cho, Sunghwan; Lee, Sangyeop; Kwon, Jimin; Son, Hye Bin; Song, Jun Hyuk; Lee, Dong‐Gue; Song, Gyujin; Lee, Sang‐Young; Jung, Sungjune; Park, Soojin; et al.
Abstract: Stretchable electronics have been considered a key technology in wearable and implantable medical devices. Although substantial advances have been made in key stretchable components, a stretchable electronic platform that integrates a stretchable power source and a stretchable printed circuit board (SPCB) has been a great challenge. Here, an intrinsically stretchable electronic device platform powered by a stretchable film battery is proposed so that the platform can be used as a stand‐alone. The stretchable battery is used as a substrate for manufacturing device platforms where SPCB is printed and directly connected through via holes, thereby enabling an increase in integrated devices density. To achieve an intrinsically stretchable battery and high‐performance circuit board, a novel concept of stretchable, self‐healable, and pressure‐sensitive polymer composite is designed. The platform is water‐proof and maintains its stable electrical performance under extreme physical deformations. As a proof of concept, the integration of light‐emitting diodes on the platform that can operate at large biaxial strain (125%) underwater is demonstrated. Abstract : A new concept of a stretchable electronic device platform, a self‐powered stretchable battery printed circuit board is proposed. The all‐component stretchable battery that provides stable electrochemical cycling performance under large strain is used as the power source and stretchable substrate, and stretchable circuits are directly printed on top to instantly form a stable interface and maintain its electrical performance under deformations.